2009
DOI: 10.1364/oe.17.004019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of image quality on tissue thickness measurements obtained with spectral domain-optical coherence tomography

Abstract: The purpose of this study was to investigate the effect of image quality on retinal nerve fiber layer (RNFL) and retinal thickness measurements obtained using three commercially available spectral-domain optical coherence tomographers (SD-OCT). Subjectively determined good, medium and poor quality images were obtained from four healthy and one glaucoma suspect eyes. RNFL and retinal thickness measurements were compared as a function of image quality. Results indicate that when image quality is within the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 20 publications
4
68
0
Order By: Relevance
“…The MSI parameters are not only useful for providing immediate feedback of signal quality to users during data acquisition, but they are also found to be important determinants of automated tissue layer segmentation accuracy. Several studies in time domain [5][6][7][8] and spectral domain 9,10 OCTs reported correlation between MSI values with retinal nerve fiber layer and retinal thickness measurements. In addition, manufacturers usually recommend a threshold for their MSI values, below which the automatic measurement results may not be reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSI parameters are not only useful for providing immediate feedback of signal quality to users during data acquisition, but they are also found to be important determinants of automated tissue layer segmentation accuracy. Several studies in time domain [5][6][7][8] and spectral domain 9,10 OCTs reported correlation between MSI values with retinal nerve fiber layer and retinal thickness measurements. In addition, manufacturers usually recommend a threshold for their MSI values, below which the automatic measurement results may not be reliable.…”
Section: Discussionmentioning
confidence: 99%
“…OCT scans were exported from the respective manufacturer software in raw format and analyzed using a custom-developed MATLAB program (Mathworks, Natick, MA). Procedures of exporting raw pixel values were similar to those used by other research groups, 10 and the data were saved in single (float) precision in MATLAB. Histogram plots were obtained by binning the pixel intensity into 512 steps of equal distance across the data range.…”
Section: Quantitative Assessmentmentioning
confidence: 99%
“…Measurements were performed before and after anti-VEGF treatment. For images to be included in the present study, the signal-to-noise ratio (SNR) had to be at least 20 dB (considered best quality) and should be taken as close to the fovea as possible (thinnest macular point), with the understanding that slight differences in positioning affect the measured thicknesses (21) . Using the Spectralis linear measurement tool, two independent observers measured CT perpendicularly from the outer edge of the hyper-reflective RPE to the inner sclera at 500-mm intervals temporal and nasal to the fovea up to 1,000 mm.…”
Section: Choroidal Thickness Measurementmentioning
confidence: 99%
“…The simulated dataset consists of 100 images generated according to the proposed model with different values of peak signal to noise ratio (PSNR) (30,25,20, and 15 dB) (PSNR ¼ 10 log 10 fmax ðImageÞ 2 ∕E½ðNoiseÞ 2 g). Figure 3 presents an example of a simulated image.…”
Section: Datasetsmentioning
confidence: 99%
“…[17][18][19] In Ref. 20, authors showed that the instrument built-in segmentation software is relatively robust to the image quality and the noise may lower the accuracy of the RNFL layer thickness estimation. However, the detection of glaucoma progression with optical coherence tomography (OCT) remains a challenge because when assessing structural changes over time, it is difficult to discriminate between glaucomatous structural damage and measurement variability.…”
Section: Introductionmentioning
confidence: 99%